Hydro, hydrogeological constraints to managed aquifer recharge in the Indo Gangetic Plains. - Prathapar, Sanmugam A.; Sharma, Bharat R.; Aggarwal, Pramod K. (International Water Management Institute, 2012)
Groundwater irrigation over the past few decades has improved stability in cropping but resulted in aquifer depletion in semi-arid regions of India. To minimize decline of groundwater levels, Managed Aquifer Recharge (MAR) interventions are widely adopted, supported by local communities, state and central governments. Albeit a desirable intervention, there is overwhelming evidence that many of the MAR structures are excessively designed, poorly located and therefore reflect poor investment of valuable human and financial resources. This paper identifies hydro and hydrogeological factors which dictate the performance of MAR intervention. The influence of annual rainfall, available land and water, river-aquifer interaction, soil, and aquifer types on MAR is discussed.